Physical training of football players based on their positional rules in the team. Effects on performance-related factors - Di Salvo, V.; Pigozzi, F. (The Journal of Sports Medicine and Physical Fitness, 1998)
AIM: The aim of this study was to evaluate the relative effectiveness of an individualized training programme for football players according to their positions in the team, by comparing it with a programme which did not differentiate roles, but utilized the same means for training. METHODS: Forty-four young top level football players divided equally into an experimental and a control group were submitted to two different training programmes for an 8-month period. Each group consisted of 5 forwards, 6 midfielders, 4 fullbacks, 4 centerbacks and 3 goalkeepers. The two groups had almost the same average age (17.8 +/- 0.6 and 17.7 +/- 0.6 yrs respectively), weight (72.6 +/- 4.7 and 72.8 +/- 3.7 kg) and height (181.3 +/-4.4 and 180.3 +/- 4.0 cm). The following measurements were taken before and after the training period in order to evaluate the aerobic and anaerobic (lactacid and alactacid) power as well as explosive and elastic power which are related to football performance: running tests of 30, 50, 300 and 1,000 meters, squat jump (SJ), counter movement jump (CMJ) and repetition counter movement jump (test 15"). RESULTS: A percent improvement observed for forwards and centerbacks was significant, in comparison with the control group, in all tests but the 30 and 1,000 meters run, on the contrary fullbacks and midfielders demonstrated a significant improvement only in the 1000 m run test (p < 0.01). In addition, a significant increase (14%, p < 0.01) was observed in CMJ of goalkeepers in the experimental group, in comparison with the control group. CONCLUSIONS: It is concluded that individualized training developed in accordance with the real model of football performance and the different mechanisms of bioenergetic processes, is a superior method of training and can optimise the performance of all player in the team.